Sweat rate and fluid intake in young elite basketball players on the FIBA Europe U20 Championship - Vukasinovic Vesic, Milica Djordje; Andjelković, Marija; Stojmenović, Tamara; Dikić, Nenad; Kostić, Marija; Ćurčić, Djordje (Vojnosanitetski pregled, 2016)
Background/Aim. Previous investigations in many sports indicated that continued exercise, especially in hot environments, can cause high sweat rate and huge water and electrolyte losses, thus impairing the performance of athletes. Most these studies were conducted during training sessions, but rarely during an official competition. Therefore, the aim of our study was to determine pre- and post-competition hydration, fluid intake and sweat loss of young elite basketball players during the FIBA Europe U20 Championship. Methods. The study included 96 basketball male players, (19 ± 0.79 years) of eight national teams. Ambient temperature was 30 ± 2ºC, humidity 55 ± 4% and the mean playing time in game 18.8 ± 10.5 min. The following parameters related to hydration status were measured: fluid intake, urine output, sweat rate, percent of dehydration, urine parameters (specific gravity, color and osmolarity), body mass and body surface area. Results. We found that the mean fluid intake was 1.79 ± 0.8 L/h, sweat rate 2.7 ± 0.9 L/h, urine output 55 ± 61 mL and the percentage of dehydration 0.99 ± 0.7%. According to urine osmolarity more than 75% of players were dehydrated before the game and the process continued during the game. The difference in body mass (0.9 ± 0.7 kg) before and after the game was statistically significant. There were statistically significant correlations between the sweat rate and fluid intake, urine osmolarity, body mass loss, body surface area and percentage of dehydration. Fluid intake correlated with the percentage of dehydration, body mass loss, urine specific gravity and urine color. The sweat rate, which varied between the teams, was the highest for centers when this parameter was calculated on the effective time in game. Conclusion. Most of the athletes start competition dehydrated, fail to compensate sweat loss during the game and continue to be dehydrated, regardless what kind of drink was used. These results suggest that hydration strategies must be carefully taken into account, not only by the players, but also by the coaches and the team doctors. Key words: basketball; water-electrolyte balance; sweating; dehydration; europe.